Is there evidence of pessimism and doubt in subjective distributions? A comment on Abel - Paolo Giordani; Paul Söderkind (Stockholm School of Economics, The Economic Research Institute (EFI), 2002)
Abel (2002) shows that pessimism and doubt in the subjective distribution of the growth rate of consumption reduce the riskfree rate puzzle and the equity premium puzzle. We quantify the amount of pessimism and doubt in survey data on US consumption and income. Individual forecasters are in fact pessimistic, but show marked overconfidence rather than doubt. Whether this implies that overconfidence should be built into Abel's model depends on how the empirically heterogeneous subjective distributions are mapped into the distribution of a fictitious representative agent. We work out the form of this mapping in an Arrow-Debreu economy and show that the equity premium increases with the dispersion of beliefs. We then estimate this aggregate distribution and find little evidence of either overconfidence or doubt.
Keywords: C42; E44; G12; 330; equity premium; riskfree rate; aggregation of beliefs; Survey of Professional Forecasters; Livingston Survey; Risikoprämie; Risiko; Schätzung